Aronia melanocarpa (Michaux) Elliot Fruit Juice Attenuates Acetaminophen-induced Hepatotoxicity on Larval Zebrafish Model - Gülçin Çakan Akdoğan; Çiğdem Bilgi (Journal of Agricultural Sciences)
Aronia melanocarpa (Michaux) Elliot (chokeberry) is a natural medicinal plant with a rich content of phenolic compounds such as procyanidins, anthocyanins, and phenolic acids. Chokeberry fruits are gaining worldwide popularity due to the strong bioactivities of their phenolic constituents, such as antioxidant, anti-inflammatory, anticancer, and liver-protective effects.In the present study, total phenolic, flavonoid, and anthocyanin contents of chokeberry juice were determined via the Folin-Ciocalteu method, a spectrophotometric method based on AlCl3 complexation, and pH differential method, respectively. Anthocyanin content was determined as 1.14% (equivalent to cyanidin-3-glucoside), while phenolic and flavonoid contents were measured as 5060.87 and 331.03 mg per 100 g of freeze-dried juice (equivalent to gallic acid and quercetin), respectively.The hepatoprotective effects of chokeberry fruit juice were evaluated using a zebrafish in vivo model for acetaminophen (APAP)-induced liver injury. Zebrafish is an emerging in vivo liver injury model that enables hepatoprotective bioactivity screening of samples on live organisms.The APAP-induced liver injury model was established by treating zebrafish larvae with 5 mM APAP from 2 days post fertilization (dpf) to 5 dpf. The hepatoprotective effect of chokeberry was evaluated via exposure to 1, 10, and 100 μg/mL of fruit juice. While chokeberry fruit juice did not cause any toxicity up to 100 μg/mL, it successfully reduced the injury induced by APAP when applied at 1 μg/mL concentration. To our knowledge, this is the first report evaluating the hepatoprotective effects of chokeberry using zebrafish in vivo liver injury model.